PERAN TANAMAN HERBAL SEBAGAI TERAPI TAMBAHAN DALAM PENANGANAN ASMA: TINJAUAN SISTEMATIS LITERATUR - Nazwa Aliefia Adzani; Riki Nova (Nusantara Hasana Journal, 2025)
Asthma is a chronic inflammatory respiratory disease that poses major challenges in its diagnosis and management. Modern asthma therapy has limitations, especially the side effects of synthetic drugs. Therefore, the use of herbal plants as an additional therapy is a potential alternative. This article is a literature review using the systematic review method with the PRISMA diagram. The literature was searched through the Google Scholar and PubMed databases using the keywords "herbal plants", "therapy", and "asthma" for publications in 2014–2024. Articles were selected based on relevant inclusion and exclusion criteria. A total of 15 selected journals discuss various herbal plants that have anti-asthma potential, including black cumin (Nigella sativa), ground cherry (Physalis angulata L.), betel leaf (Piper betle L.), sembung leaf (Blumea balsamifera L.), cubeb fruit (Piper cubeba L.), sedge rhizome (Cyperus rotundus L.), patikan kebo herb (Euphorbia hirta L.), and widuri leaf (Calotropis gigantea). The mechanism of action of these plants involves anti-inflammatory, immunomodulatory activity, as well as reducing inflammatory mediators such as TNF-α, IL-4, IL-5, IL-13, and IgE. Herbal plants have significant potential as additional therapy for asthma through anti-inflammatory and immunomodulatory mechanisms. Further research in the form of clinical trials is still needed.